Artificial Intelligence and the clustering of human capital: The risks for Europe - Björn Brey; Erik Van der Marel (European Centre for International Political Economy (ECIPE), 2023)
Europe trails the global frontier of productivity growth and the region's trend is sluggish. Much prospective economic growth for Europe is likely to come from AI and its adoption by European firms which is projected to shoot up the productivity trend. For such AI-generated growth to work, high levels of human capital need to be available for firms, in particular Science, Technology, Engineering, and Mathematics (STEM) graduates. However, much of this human capital for AI is leaving Europe and the region experiences a net outflow when it comes to the skills required to make AI work. Moreover, the spread of both human capital and AI is very uneven within Europe, with some in the West spearheading whilst others in the East are trailing. This paper shows that those regions in Europe that successfully have invested in human capital in the past explain more than one-third of AI adoption by their firms a decade later. Furthermore, this persistent trend is driven by the most human capital-intense firms as they explain more than 50 percent of the observed adoption of AI across Europe. The clustering of human capital is very persistent over time and those that lag in human capital now will weigh down Europe's ability in generating AI-related growth in the future. This will likely have long-lasting effects for Europe as a whole, defining its capacity to catch up to the global frontier or amplifying the region's slow-moving growth and productivity trend. Policy makers who are serious about creating growth in the future on the back of AI should therefore invest in human capital now, or else Europe will further fall behind.
Keywords: 330; Artificial intelligence; human capital; productivity development; economic growth; innovation diffusion; EU member states; Künstliche Intelligenz; Humankapital; Produktivitätsentwicklung; Wirtschaftswachstum; Innovationsdiffusion; EU-Staaten